Zeb1 Regulates the Symmetric Division of Mouse Lewis Lung Carcinoma Stem Cells through Numb mediated by miR-31 - Wang, Jianyu (Int J Biol Sci, 2018)
Symmetric cell division (SD) and asymmetric cell division (ASD) were the unique characteristics of stem cells and the mechanisms underlying stem cell renewal. While recent studies have identified the presence of SD and ASD in lung cancer stem cells (CSCs), the mechanisms regulating SD and ASD in cancer state have not been elucidated, mostly due to the lack of stable cellular models of SD and ASD in CSC research. In this study, the interaction between Zeb1, an Epithelial-Mesenchymal Transition (EMT) factor shown to regulate CSCs self-renew, and Numb, which regulates SD and ASD in the normal neural stem cell was investigated using the stable mouse Lewis lung adenocarcinoma SD (LLC-SD) and ASD (LLC-ASD) lines established from our previous study. The most significant finding derived from this line of research is that we have identified and molecularly ordered the axis of Zeb1-miR-31-Numb that regulates the SD, a mechanism of CSC self-renewal that has not been previously described. More specifically, the expression of Zeb1 and Numb were both significantly higher in LLC-SD than LLC-ASD cells. Silencing of Zeb1 or Numb expression lead to decreased ratio of SD and weakened single-cell cloning formation, tumor growth and tumor metastasis, respectively. The rescure experiments have molecularly ordered the regulation of Numb by Zeb1, indirectly mediated by miR-31. Moreover, we also provided preliminary evidence supporting the clinical relevance of our finding. In summary, our study provides a new insight for the self-renew of lung CSCs in which SD is regulated by the axis of Zeb1-miR-31-Numb.